Complex Multiple‐Nucleotide Substitution Mutations Causing Human Inherited Disease Reveal Novel Insights into the Action of Translesion Synthesis DNA Polymerases. Issue 11 (3rd August 2015) - Chen, Jian‐Min; Férec, Claude; Cooper, David N.
<x xml:space="preserve">Abstract</x> Translesion synthesis (TLS) DNA polymerases allow the bypass of unrepaired lesions during DNA replication. We have recently postulated new properties of TLS DNA polymerases in DNA repair: the generation of neo‐microhomologies potentiating strand‐misalignment and additional micro‐lesions within the templated inserts when recruited to stalled replication forks. Here, we provide further support for this postulate and illustrate how repeated participation of TLS DNA polymerases could convert a damaged base into a complex lesion through a process of successive template switching and bypass repair.